Compatibility of Border Meeting of Two Layers Protocol (BGP Version 4) With IPV6 (International Journal of Engineering and Computer Science, 2018)
This paper deals with issues, which network designers, would have to deal with once IPV6, which is the layer 3 Internet Protocol of the future comes into mass existence. IPV6 will have compatibility issues with most of the existing routing protocols especially with Border Gateway Protocol (BGPV4), which is a layer 7 protocol on which the backbone of the Internet runs. BGP Version 4 is an interdomain routing protocol. The primary function of BGP is to provide and exchange network reachability information between Autonomous Systems (AS).